2013
DOI: 10.1515/cjal-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety: Past and Future

Abstract: This paper gives a comprehensive review of studies on foreign language anxiety. Foreign language anxiety has been recognized in the past few decades as a situation-specific emotional reaction that potentially impedes foreign language learning. Research has shown that foreign language anxiety is not only prevalent among foreign language learners, but also has various negative effects on foreign language learning. In order to help learners cope with this problem, researchers have identified a large number of sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
0
12
0
2
Order By: Relevance
“…This, accordingly, would be an obstruction to the student to achieve a high level of speaking English more confidently and the expected learning outcomes. (Worde, 2003& Luo, 2013 consider speaking anxiety as a potential problem that can affect the production and retention of learner"s new language.…”
Section: Introductionmentioning
confidence: 99%
“…This, accordingly, would be an obstruction to the student to achieve a high level of speaking English more confidently and the expected learning outcomes. (Worde, 2003& Luo, 2013 consider speaking anxiety as a potential problem that can affect the production and retention of learner"s new language.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that one-third of the foreign language learners experience at least a moderate level of foreign language anxiety [2]. Researchers have also documented the wide range of potential negative effects that foreign language anxiety has on foreign language learning [3]. Among the four skills of acquiring a language (reading, listening, speaking and writing), speaking has been identified as a high-anxiety proficiency [1], [4], [5], and the anxiety debilitates the oral performance of second language learners [6].…”
Section: Introductionmentioning
confidence: 99%
“…The students can not speak well because the student feel confuse and sometime because of English is not their mother language for them.They feel anxiety, it is called language anxiety. Luo (2013) stated Language anxiety is the problem when the students feel fear they going to practice their English. Ansari (2015) said that foreign language anxiety are psychological, behaviorial, and knowledge related responses that accompany an individuals feelings as result of his or her own negative expectation and failure in term of negative performance related to foreign language learning.…”
Section: Introductionmentioning
confidence: 99%